FINANCIAL SUPPORT FOR THE DEVELOPMENT OF RENEWABLE ENERGY: INTERNATIONAL EXPERIENCE AND CURRENT INVESTMENT MECHANISMS (INNOVATIVE ECONOMY, 2026)
Verbitska I.I., Shmyhel O.Ye. FINANCIAL SUPPORT FOR THE DEVELOPMENT OF RENEWABLE ENERGY: INTERNATIONAL EXPERIENCE AND CURRENT INVESTMENT MECHANISMSPurpose. The aim of the article is to explore modern mechanisms of financial support for the development of renewable energy based on the analysis of international experience, assessment of investment instruments and identification of promising directions of capital attraction in the conditions of global energy transition.Methodology of research. A complex of general scientific and special methods was used in the research process. A systematic approach was applied to the analysis of financial support for renewable energy as a multi-level economic system. Methods of comparative analysis and generalization were used to study international financial mechanisms for supporting renewable energy. Statistical and dynamic analysis made it possible to assess the trends of global investments in clean energy and fossil fuels during 2015–2025. The logical and structural approach was used to form an integrated analytical model for assessing the effectiveness of financing for renewable energy projects.Findings. The main international and domestic mechanisms for financing the development of renewable energy have been systematized. Their economic advantages, functional limitations, and suitability for use depending on the scale of the renewable energy project have been identified. The dynamics of global investments in clean energy and fossil fuels have been analysed, confirming a steady trend toward the reorientation of international capital toward low-carbon technologies. The feasibility of the comprehensive use of blended finance, ESG-oriented instruments, and international credit mechanisms as key factors in ensuring the energy transition has been substantiated. An integrated analytical system for evaluating the effectiveness of renewable energy financing is proposed, combining traditional financial instruments, alternative capital mobilization models, and AI-oriented risk management mechanisms.Originality. The theoretical and methodological foundations of financial support for the development of renewable energy have been further explored through the development of an integrated approach to assessing the effectiveness of financing for renewable energy projects. A mechanism has been proposed that combines traditional financing instruments (project financing, green bonds, bank loans), alternative capital mobilization mechanisms (microfinance, crowdfunding, blended finance), and digital risk forecasting tools based on AI models into a unified system for assessing the financial sustainability of renewable energy projects. The approach to analysing the investment attractiveness of renewable energy has been refined by taking into account not only the cost of capital but also ESG factors, regulatory volatility, climate risks, and the dynamics of global financial flows.Practical value. The practical significance of the study’s findings lies in the potential for government agencies, international financial institutions, banks, energy companies, and private investors to utilize the proposed approaches when developing financing strategies for renewable energy projects. This will make it possible to improve the accuracy of investment efficiency assessments, optimize capital structure, reduce financial risks, improve the investment process, and strengthen the financial stability of energy projects in conditions of macroeconomic instability. The study’s findings can also be used in the development of government programs to support renewable energy, investment guarantee mechanisms, and models for the development of decentralized energy.Key words: financing, renewable energy, energy financing, green bonds, project financing, international financial institutions, energy transition, investment mechanisms, ESG financing, micro-financing, crowd-investing, AI risk management models, decarbonization.
Keywords: financing; renewable energy; energy financing; green bonds; project financing; international financial institutions; energy transition; investment mechanisms; ESG financing; micro-financing; crowd-investing; AI risk management models; decarbonization